Expression of α-Tubulin Acetyltransferase 1 and Tubulin Acetylation as Selective Forces in Cell Competition - Amir Mohammad Rahimi; Mingfang Cai; Irem Kılıҫ; Zahra Basir Kazerouni; Constanza Tapia Contreras; Sigrid Hoyer-Fender (Cells, 2021)
The wound healing response of fibroblasts critically depends on the primary cilium, a sensory organelle protruding into the environment and comprising a stable axonemal structure. A characteristic marker for primary cilia is acetylation of axonemal tubulin. Although formation of primary cilia is under cell cycle control, the environmental cues affecting ciliation are not fully understood. Our purpose was, therefore, to study the impact of culture conditions on cilia formation in NIH3T3 fibroblasts. We quantified ciliation in different NIH3T3 sub-cell lines and culture conditions by immunodetection of primary cilia and counting. Quantitative Western blotting, qRT-PCR, and proliferation assays completed our investigation. We observed large differences between NIH3T3 sub-cell lines in their ability to generate acetylated primary cilia that correlated with cytoplasmic tubulin acetylation. We found no increased activity of the major tubulin deacetylase, HDAC6, but instead reduced expression of the α-tubulin acetyltransferase 1 (Atat1) as being causative. Our observations demonstrate that cells with reduced expression of Atat1 and tubulin acetylation proliferate faster, eventually displacing all other cells in the population. Expression of Atat1 and tubulin acetylation are therefore selective forces in cell competition.